Etiquette and taboos around the world : a geographic encyclopedia of social and cultural customs - Taylor, Ken, 1953-; Williams, Victoria (Santa Barbara, California : Greenwood, an imprint of ABC-CLIO, LLC, 2017)
"An interesting resource for learning about the cultural differences and characteristics of people across the globe, this encyclopedia covers the "do's" and "don'ts" of a breadth of countries and major ethnic groups. Readers of this one-volume reference will gain useful knowledge of what travelers should and shouldn't do when in countries outside of the United States. After a general introduction, approximately 100 alphabetically arranged entries cover topics such as greeting and meeting, appearance and dress, table manners, body language, social situations and hospitality, verbal communications, business etiquette, religious etiquette, gift-giving, and even "netiquette" regarding social media." --publisher description.
African American -- Algeria -- Arabian Peninsula -- Argentina -- Armenia -- Australia -- Balkan Peninsula, Western -- Bangladesh -- Basque -- Bedouin -- Belgium -- Berbers -- Bolivia -- Brazil -- Bulgaria -- Canada -- The Caribbean -- Central Africa -- Central America -- Chile -- China -- Colombia -- Cuba -- East Africa (Kenya, Tanzania, Uganda) -- Ecuador -- Egypt -- France -- The Fulani -- Germany, Austria, and German-speaking Switzerland -- Great Britain -- Greece -- Gujarat -- Hmong -- Horn of Africa (Djibouti, Eritrea, Ethiopia, Somalia) -- Hui -- Hungary -- Hutu and Tutsi -- India -- Indonesia -- Iran and Central Asia -- Ireland -- Israel -- Italy -- Jamaica -- Japan -- Karens -- Khmer -- Libya -- Madagascar -- Maori -- Masai -- Mexico -- Mongolia -- Morocco -- Myanmar -- Native Americans, Plains Indians -- Native Americans, Southwest -- The Netherlands -- New Zealand -- Nigeria -- Pacific Islanders -- Pakistan -- Palestine -- Papua New Guinea -- Pashtuns -- Peru -- The Philippines -- Poland -- Portugal -- Punjab -- Quechua -- Roma -- Russia -- Scandinavia -- Singapore -- South Korea -- Southern Africa -- Spain -- Spanish-speaking Caribbean: Puerto Rico and the Dominican Republic -- Tajikistan -- Tamils -- Thailand -- Tibet -- Tuareg -- Turkey -- Ukraine -- Uyghurs -- Uzbekistan -- Venezuela -- Vietnam -- Western Africa -- Zhuang -- Zulu and Xhosa.
Includes bibliographical references and index.
Keywords: Etiquette -- Encyclopedias; Taboo -- Encyclopedias; SOCIAL SCIENCE / Customs & Traditions; SOCIAL SCIENCE / Ethnic Studies; SOCIAL SCIENCE / Human Geography; Etiquette -- Encyclopedias; Taboo -- Encyclopedias; Encyclopedias